2020
DOI: 10.1021/acsomega.0c01670
|View full text |Cite
|
Sign up to set email alerts
|

Antiarthritic Potential of Comprehensively Standardized Extract of Alternanthera bettzickiana: In Vitro and In Vivo Studies

Abstract: Alternanthera bettzickiana is being used as a folk remedy for treating arthritis by conventional healers in Thailand. The current research was undertaken to explore the antiarthritic potential of A. bettzickiana ethanolic extract (ABEE). Plant characterization, molecular docking, and in vitro and in vivo (ABEE at 250, 500, and 1000 mg/kg was administered orally to rats once daily for 28 days) studies to explore the antiarthritic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 69 publications
0
26
1
Order By: Relevance
“…This augmented level of PGE 2 accelerates the differentiations of osteoclast and generating the degrading enzymes and hence stimulates the bone erosion, vasodilation and migration of leukocytes at site of in ammation. So, any substance that prevents the generations of aforementioned mediators carries great importance in the management of rheumatism (Manan et al, 2020). In current study, increased expression of COX-2 and PGE-2 were noted in diseased controlled rats, however, signi cant decrease in COX-2 and prostaglandin-E2 were observed in rats treated with nerolidol.…”
Section: Discussioncontrasting
confidence: 44%
“…This augmented level of PGE 2 accelerates the differentiations of osteoclast and generating the degrading enzymes and hence stimulates the bone erosion, vasodilation and migration of leukocytes at site of in ammation. So, any substance that prevents the generations of aforementioned mediators carries great importance in the management of rheumatism (Manan et al, 2020). In current study, increased expression of COX-2 and PGE-2 were noted in diseased controlled rats, however, signi cant decrease in COX-2 and prostaglandin-E2 were observed in rats treated with nerolidol.…”
Section: Discussioncontrasting
confidence: 44%
“…They have found that even the 250 mg/kg/day of the ethanolic extract was able to modulate the parameters suggesting the antiarthritic potential when compared with standard drug and disease control. In silico analysis suggested the strong interaction between the HPLC-analysed phytomolecules and cyclooxygenases ( Manan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The quercetin inhibits CNS and spinal cord glial cells activation, and consequently reduces cytokine production and oxidative stress resulting in reduced neuro-in ammation and hyperalgesia [30]. Catechin, belonging to the avonoid family, can alleviate the in ammation and pain response in rats by decreasing the generation of TNF-α, PGE2, and IL-1β [31].We now know that circulating matrix metalloprotease 9 (MMP-9) plays an important role in neuro-in ammation and oxidative stress as two leadings factors of the neuropathic pain. It has been proved that Catechin reduces MMP-9 in diabetic rats [1].…”
Section: Discussionmentioning
confidence: 99%